Invasive potential of C3-C4 intermediate Parthenium hysterophorus under elevated CO2 - NAIDU, V SGR (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted in open top chambers (OTCs) to study the growth, water-use efficiency and carbonisotope discrimination (Î”13C) in Parthenium hysterophorus in response to elevated CO2. Parthenium plants were grownin OTCs maintained at ambient (370Â±20 ppm) and elevated (550Â±30) CO2 levels as well as under open field conditions.Water-use efficiency (WUE) was determined by gravimetric method. The carbon isotope discrimination (Î”13C) wasdetermined by Isotope Ratio Mass Spectrometry (IRMS). The CO2 enrichment enhanced both the above and below groundbiomass in Parthenium. Water-use efficiency (WUE) and Carbon isotope discrimination (Î”13C) were higher in plantsgrown under elevated CO2 compared to plants under ambient CO2 conditions. The growth stimulation and increasedwater-use efficiency in Parthenium indicates that this weed could become more aggressive in future if the atmosphericCO2 continue to rise coupled with the rise in temperature.